Differential expression of extracellular matrix genes in glenohumeral capsule of shoulder instability patients. (3rd July 2016) - Belangero, Paulo Santoro; Leal, Mariana Ferreira; Figueiredo, Eduardo Antônio; Cohen, Carina; Andreoli, Carlos Vicente; Smith, Marília Cardoso; Pochini, Alberto de Castro; Ejnisman, Benno; Cohen, Moises
ABSTRACT: Anterior shoulder instability is a common orthopedic problem. After a traumatic shoulder dislocation, patients present a plastic deformation of the capsule. The shoulder instability biology remains poorly understood. We evaluated the expression of genes that encode the cartilage oligomeric matrix protein ( COMP ), fibronectin 1 ( FN1 ), tenascin C ( TNC ) and tenascin XB ( TNXB ) in the glenohumeral capsule of anterior shoulder instability patients and controls. Moreover, we investigated the associations between gene expression and clinical parameters. The gene expression was evaluated by quantitative reverse transcription-polymerase chain reaction in the antero-inferior (macroscopically injured region), antero-superior and posterior regions of the capsule of 29 patients with shoulder instability and 8 controls. COMP expression was reduced and FN1 and TNC expression was increased in the antero-inferior capsule region of cases compared to controls ( p < 0.05). TNC expression was increased in the posterior capsule portion of shoulder instability patients ( p = 0.022). COMP expression was reduced in the antero-inferior region compared to the posterior region of shoulder instability patients ( p = 0.007). In the antero-inferior region, FN1 expression was increased in the capsule of patients with more than one year of symptoms ( p = 0.003) and with recurrent dislocations ( p = 0.004) compared with controls. FN1 and TNXB expression was correlated with the duration of symptoms in the posterior region ( p < 0.05). Thus, COMP, FN1, TNC and TNXB expression was altered across the capsule of shoulder instability patients. Dislocation episodes modify FN1, TNC and TNXB expression in the injured tissue. COMP altered expression may be associated with capsule integrity after shoulder dislocation, particularly in the macroscopically injured portion.